Power-Efficient ASIC Implementation of Double SHA-256 for Proof of Work Mining - Lim Yong Fong; Shahidatul Sadiah; Ab Al-Hadi Ab Rahman; Muhammad Mun’im Ahmad Zabidi; Mohd Usairy Syafiq (ELEKTRIKA- Journal of Electrical Engineering, 2025)
In this paper, a design space exploration is performed aiming at implementing a low power and high-performance hardware architecture for the double SHA-256 accelerator with optimized message scheduler. Furthermore, this study also explores the power optimization of this architecture by enabling clock gating during logic synthesis and using High Voltage Threshold (HVT) standard cells for layout implementation. The 32nm version of the SAED process design kits (PDK) was used for the ASIC implementation of the double SHA-256 hash function. The result shows that the combination of using HVT standard cell and disabling clock gating achieved the most-balanced trade-off between performance and power consumption. The resulting design could obtain a throughput of 187.9 Gbps at the frequency of 183.5 MHz with power consumption of 131.9 mW.